2018
DOI: 10.1111/eos.12537
|View full text |Cite
|
Sign up to set email alerts
|

Shear fatigue strength of resin composite bonded to dentin at physiological frequency

Abstract: The purpose of this study was to examine the shear fatigue strengths of a resin composite bonded to dentin. Three adhesive systems - a two-step self-etch adhesive (OptiBond XTR; Kerr) and two universal adhesives [Scotchbond Universal (3M ESPE) and G-Premio Bond (GC)] - were used in self-etch mode to bond a resin composite to dentin at a physiologic frequency of 2 Hz over 50,000, 100,000, and 1,000,000 cycles. A staircase method of fatigue testing was used. Twenty specimens were used for each test condition. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…Development started with Erickson et al [10,11] and was refined by researchers from NU and CU (Barkmeier et al [12], Takamizawa et al [13], and Tsujimoto et al [14]). The appropriate frequency [13,15], number of cycles [14], and analysis are now well-established. However, at the present time, research comparing the bonding performance of universal adhesives using this bond fatigue test for either etch-and-rinse or self-etch mode has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Development started with Erickson et al [10,11] and was refined by researchers from NU and CU (Barkmeier et al [12], Takamizawa et al [13], and Tsujimoto et al [14]). The appropriate frequency [13,15], number of cycles [14], and analysis are now well-established. However, at the present time, research comparing the bonding performance of universal adhesives using this bond fatigue test for either etch-and-rinse or self-etch mode has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies applied a cycling rate between 1 and 2 Hz because chewing rate in humans mostly reported was below 2 Hz [43]. Tsujimoto et al [44] stated that the use of physiologic frequency rates for fatigue studies conducted in the laboratory is a challenge because of time requirements. The loading frequency applied in the present study is in accordance with other researches [21,22,45,46] which applied higher rates because the duration of mastication force is reported to be from 0.25 to 0.33 seconds and also to ensure full application of the load.…”
Section: Discussionmentioning
confidence: 99%
“…This estimate is much longer than one calculated directly from cycles. A previous study reported that a person makes approximately 2700 chewing cycles per day, or approximately 1,000,000 cycles per year [28]. In addition, another study reported that 1,200,000 cycles are often used to simulate a service time of 5 years [29].…”
Section: Discussionmentioning
confidence: 99%